2011
DOI: 10.1038/bmt.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

Tear physiology in dry eye associated with chronic GVHD

Abstract: The purpose of this study was to compare tear physiology characteristics of chronic GVHD (cGVHD)-associated dry eye to dry eye caused by Sjogren's syndrome (SS), a extreme form of aqueous-deficient dry eye, and meibomian gland dysfunction (MGD), the major cause of evaporative dry eye. Tear turnover rate, evaporation and osmolarity along with meibomian gland dropout and lipid layer interferometric patterns were assessed in the right eyes of 12 patients with dry eye associated with cGVHD, 12 age-matched patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Researchers have reported that subjects with SS have decreased meibum expressibility and quality [38], as well as increased meibomian gland dropout [39, 40] and dysfunction [38, 40, 41]. Further, SS patients have a reduced volume [1, 42], stability [39], lipid layer [39], and surface activity [43] of tears, heightened tear film evaporation [44, 45], ocular surface damage [1, 42], and increased DED symptoms [1, 41]. In effect, as indicated by Akpek et al [46], SS patients have combined aqueous and evaporative DED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have reported that subjects with SS have decreased meibum expressibility and quality [38], as well as increased meibomian gland dropout [39, 40] and dysfunction [38, 40, 41]. Further, SS patients have a reduced volume [1, 42], stability [39], lipid layer [39], and surface activity [43] of tears, heightened tear film evaporation [44, 45], ocular surface damage [1, 42], and increased DED symptoms [1, 41]. In effect, as indicated by Akpek et al [46], SS patients have combined aqueous and evaporative DED.…”
Section: Discussionmentioning
confidence: 99%
“…Such conjunctival inflammation may create a toxic environment, leading to the release of proinflammatory cytokines that impact the terminal duct of the meibomian gland and cause other pathophysiological sequelae on the ocular surface. These effects are known to occur in severe atopy [18], Stevens-Johnson syndrome [19-21], and graft-versus-host disease [22, 23], conditions that are sometimes (e.g., graft-versus-host disease) [24-27], but not necessarily, associated with androgen deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…KCS can also cause conjunctival fibrosis, lid abnormality, atrophy of meibomian glands, loss of eyelashes, and stenosis of the lacrimal punctum. [5][6][7] Therapeutic options include artificial tears, therapeutic contact lenses, punctual plugs, topical or systemic corticosteroids, and other immunosuppressive drugs. 3,6 Previous reports have demonstrated that autologous serum eye drops are effective for treating dry eye disease and have also been used for severe ocular disorders, including Sjogren and non-Sjogren syndrome, ocular surface disorders such as cicatricial pemphigoid syndrome, Steven-Johnson syndrome, and superior limbic keratitis.…”
Section: Introductionmentioning
confidence: 99%
“…6 Pathophysiology is complex, and includes fibroblastic and T-lymphocytic infiltrates in the lacrimal gland with consequent deficiency in lacrimal production owing to fibrosis. 7 DES clinical characteristics resemble those found in some autoimmune diseases (for example, Sjö gren's syndrome). 8 Despite many advances in understanding the pathophysiology, there is a paucity of good-quality studies on therapeutic options for this condition.…”
Section: Introductionmentioning
confidence: 90%